Application of Partial Models for Vibration Analysis of Combined Discrete-Continuous System - Stańczyk, T.L. (Engineering Transactions, 1994)
A method of analysis of complex dynamic systems by means of partial models is characterized in brief. Same advantages of that method as a means for analysis of combined discrete-continuous systems are pointed out. An iteration procedure for analysing such a system is presented, as well as an example of application of the method discussed for analysing a certain discrete-continuous system by its separation into partial models, for which vibration equations are formulated. The results of computation are presented. They constitute a good illustration of the convergence properties of the iteration procedure used.